Concepção, Objetivo e Método da Ciência da Religião - Tiele, Cornelis (REVER: Revista de Estudos da Religião, 2018)
Tradução de: TIELE, Cornelis. Conception, aim and method of Science of Religion. In: ______. Elements of the Science of Religion: part 1, morphological. New York: Charles Scribner’s Sons, 1897. p. 1-27.